Homeschooling: Sebuah Model Pendidikan Alternatif Berbasis Keluarga - Sadiyah Sadiyah; Anis Setiyanti; Mukti Ali; Nur Hamid; Wildan Syauqi (Institut Agama Islam Sumatera Barat, 2023)
Homeschooling is an alternative approach to education that is currently a topic of extensive discussion within the community, among parents, and among educational professionals. This discussion often revolves around concerns related to how children socialize when they are educated at home. In homeschooling, parents take on the responsibility for their child's education and are directly involved in the teaching process. Research indicates that homeschooling is gaining traction in Indonesia due to a lack of trust in formal schools. This lack of trust is rooted in concerns about constantly changing curricula, perceived burdens on students, a sense that children are treated as objects rather than active learners, limitations in nurturing children's creativity and intelligence, as well as emotional, moral, and spiritual considerations. Additionally, parents are worried about the negative external influences their children might encounter and express dissatisfaction with the formal school system. However, one notable drawback of homeschooling is that it tends to result in lower levels of horizontal socialization, meaning that homeschooled students may have limited exposure to a socially diverse and pluralistic environment. They are more likely to be isolated from broader social interactions. This study takes the form of a case study, and its main objective is to describe and understand the perceptions and backgrounds of students who participate in homeschooling, as well as to explore the challenges and issues associated with this educational approach.